O uso de smart contracts entre empresas: uma abordagem de direito e economia - Mariani, Orontes Pedro Antunes (Universidade do Vale do Rio dos Sinos, 2019)
In the 90's the lawyer and cryptographer Nick Szabo theorized about the possibility of computer protocols that could execute contractual clauses autonomously without the need for human intervention. He called it as smart contracts. With the advent of blockchain platforms, and especially with the Ethereum platform, as early as the year 2010, smart contracts came to life. Tech community started to discuss the various possibilities of application of this tool. By their turn, lawyers also entered into this debate by questioning the legality and potential benefits and problems of using smart contracts in relation to the current contractual model. Among the benefits, one of them is the autonomous fulfillment of the obligations, reducing the transaction costs. Among the problems, lawyers also say that smart contracts would have limited application to simple contracts. Complex contracts, with open clauses, inaccurate terms and many conditions would remain more affected by the traditional contract. This is the background of this dissertation. To examine this question, a qualitative survey was conducted by conducting ten interviews with people working in business management. Essentially, it was sought to verify under what conditions companies would use smart contracts in their business with other client companies and supplier companies. This cut (between companies) was chosen to avoid the incidence of laws that interfere in freedom of contracting, such as consumer law and labor law. The results demonstrate that companies would use smart contracts as a cost reduction tool in simple contracts, not necessarily because they would avoid contractual breach.
Keywords: Smart Contracts; Contratos; Descumprimento; Empresa; Blockchain; Smart Contracts; Contracts; Noncompliance; Company; Blockchain; ACCNPQ::Ciências Sociais Aplicadas::Direito